The community residents' NIMBY attitude on the construction of community ageing care service centres: a cross-sectional study - Bo Yu; Yue-Hong Han; Yin Sun; Xu-Dong Zhang (BMC, 2022)
Abstract Background China is the country with the largest elderly population. To actively respond to this ageing population, China has proposed the Community Aged Care Service Centre (CACSC) network as the major elderly care development policy. However, many residents resisted the development of the CACSC network, which affected its smooth implementation. Based on the theory of "Not in My Backyard" (NIMBY), this paper proposes a model of the influencing factors of community residents on the opposition to the construction of CACSCs. Methods Residents living in urban communities over the age of 20 in China are the target of this study. The questionnaires were collected in the form of electronic questionnaires created on a professional website, and hyperlinks to the questionnaires were distributed through social media. The descriptive statistical analysis, T-tests, ANOVA and structural equation modelling were performed on cross-sectional survey data from 509 questionnaires. Results The research results show that superstition, the NIMBY attitude, and perceived risk have a significant positive impact on the opposition to the construction of CACSCs, while the negative impact of perceived benefit on the opposition intention is not significant. Moreover, perceived knowledge has a significant positive impact on perceived benefit and a significant negative impact on superstition and perceived risk. Conclusions Strengthen policy advocacy on ageing, clarify the service content of CACSC and encourage young people to participate in public welfare activities for the elderly can reduce the opposition of community residents to the construction of a CACSC.